SYNTHESIS, CHARACTERISATION, DNA INTERACTION AND CLEAVAGE ACTIVITY OF A NOVEL SERIES OF ISOMERIC PYRIDYL-TETRAZOLE COBALT (II) COMPLEXES - B. UMAMAHESWARA RAO,; V. KRISHNA,; G. NAGESWARA RAO, (International Journal of Pharma and Bio Sciences, 2015)
A novel series of Co(II) complexes of the type Co(L1)Cl2 (1), Co(L2)Cl2 (2), Co(L3)Cl2 (3), Co(L4)Cl2 (4) were prepared with biologically active isomeric pyridyl-tetrazole ligands such as N,N-dimethyl-2-[5-(pyridin-2-yl)-1H-tetrazol-1-yl]ethanamine (L1), N,N-dimethyl-2-[5-(pyridin-2-yl)-2H-tetrazol-1-yl]ethanamine (L2), 2-[5-(pyridin-2-yl)-1H-tetrazol-1-yl]ethanol (L3), 2-[5-(pyridin-2-yl)-2H-tetrazol-2-yl]ethanol (L4) and CoCl2.H2O. in 1:1 metal ligand ratio. These complexes were characterised by elemental analysis, UV-Vis, IR, 1H, 13CNMR and mass spectral studies. EPR spectra of 1-4 cobalt complexes are characteristic of square planar geometry, DNA binding studies were carried by UV-Vis absorption, viscosity and thermal denature studies revealed that each of these complexes are avid binders of calf thymus DNA. The nucleolytic cleavage activities of complexes were carried on double stranded pBR322 circular plasmid DNA by using a gel electrophoresis experiment under various conditions, where cleavage of DNA takes place by oxidative free radical mechanism (·OH)